APPLICATIONS OF ARTIFICIAL INTELLIGENCE IN THE FIELD OF MEDIA IN LIGHT OF COMMUNICATION THEORIES - Baghdad Bendida,; Mokhter Benfetta,; Ailas Mohamed,; Reffas Noureddine,; Kadi Khalfallah, (International Journal of Innovative Technologies in Social Science, 2025)
This study explores the integration of artificial intelligence (AI) applications in the media sector through the lens of contemporary communication theories. Amid rapid technological advancements, particularly in the context of the Fourth Industrial Revolution, the media landscape is undergoing profound transformations. The research addresses the epistemological gap between classical theoretical paradigms and the dynamic reality imposed by AI-driven automation, data processing, and content generation. Adopting a descriptive-analytical methodology, this study highlights the limitations of existing media institutions, the underdeveloped infrastructure in the Arab world, and the insufficient training of journalists in AI tools. It also evaluates sociological implications through functionalist, neo-Marxist, and symbolic interactionist theories. The findings highlight the urgency of theoretical innovation, technological investment, and a unified digital culture responsive to ethical and communicative challenges.